Unconventional Energy in Argentinian Andes: Territories of Dependence or Transition? - Sofia Villalba; Alejandra Ise; Luciana Clementi (Revue de Géographie Alpine)
In the transition to sustainable energy systems, pressures arise on natural resources and territories. In Latin America, since the end of the 20th century, countries have sought to diversify their energy mixes, promoting the use of unconventional resources. In Argentina, the provinces of Neuquén and San Juan are well endowed with gas, solar and wind resources. There, large exploitation projects reposition the territories on a global and national scale. This paper aims to analyse the transition process in territories of the central Andes, considering the actors and infrastructures linked to unconventional energy resources. The main hypothesis is that regardless of the resource exploited, the projects strengthen the centralised energy system, perpetuate the inherited territorial trajectories, and thus restrict the energy transition to the replacement of energy sources. The methodological approach is based both on primary data—collected through semi-structured interviews and field observations—, and secondary data, obtained from research articles, reports and press releases. The unconventional energy resources and their associated projects in Neuquén and San Juan represent a weak transition in the territories, given the major role played by external actors and the inertia of pre-existing infrastructures.